Comparative performance of optical amplifiers: Raman and EDFA - Khalis A. Mohammed; Basma M. K. Younis (Universitas Ahmad Dahlan, 2020)
The in-line optical signal amplification is often used in optical communication systems to accomplish longer transmission distances and larger capacity. In this proposed paper, the operation of two types of optical amplifiers for 16×10 Gbps wavelength division multiplexing system had been examined by changing transmission distance from 10 to 200 km with a dispersion equals to 16.75 ps/nm/km. The analysis and design of such systems ordinarily includes many signal channels, nonlinear devices, several topologies with many noise sources, is extremely complex and effort-exhaustive. Therefore, theoretical studies with simulation CAD software of systems are become necessity to predict and optimize system performance. The comparison between EDFA and Raman has already explored by many researchers in varying ways in this work and to achieve obove objectives, the OptiSystem software was used to design the proposed fiber optic communications system and to simulate results. Performance for the present system was evaluated for parameters like bit error rate (BER), quality factor (QF), total gain with eye opening factor. It was saw that EDFA provides better results, in the maximal transmission distance 64% better than Raman amplifier, 57.5% for gain and 26.7% for maximum quality factor. As a future study a hybrid amplifier can produce better quality of amplification.